Fundamental study on the impacts of water-cooling and accumulated dust on photovoltaic module performance - Fawaz Ahmed Ali Alwesabi; Ali Saleh Aziz; Mohamad Shukor Abdul Rahim; Mohammad Faridun Naim Tajuddin; Mohd Fayzul Mohammed; Azralmukmin Azmi; Chris Satterlee; Shahrin Md Ayob; Tole Sutikno (Institute of Advanced Engineering and Science, 2022)
Photovoltaic (PV) modules have been becoming well-spread recently as alternative clean energy sources to traditional energy sources due to their efficiency and sustainability benefits. This paper applied various water temperatures and artificial dust levels to a couple of monocrystalline PV modules under outdoor conditions to observe their performance. Two different IV tracers were connected separately to each module for comparison purposes. Two temperature sensors were installed at the back of the panels to observe the cell temperatures. Besides, a temperature sensor was specified for ambient readings. Water flowed through an adjustable water-flow sensor to cool the overheated PV module using specific mass flow rates. The results indicate that the efficiency of the PV module starts to reduce when the panel temperature begins to surpass 49.1°C. It was discovered that cooling the PV module increases its efficiency from 0.97 percent at the lowest rate to 4.70 percent at the highest rate. Furthermore, accumulated dust on the PV module top surface can be reduced up to 3-fold under 110 g/m2 of dust, and up to 29.30% under 10 g/m2 of 100% of its generated energy. Improvement techniques and future work on PV module performance are also discussed.